An Investigation Into Conceptual Metaphors Used In “Gone With The Wind” By Margaret Mitchell And Its Vietnamese Translational Version Of “Cuốn Theo Chiều Gió” By Vũ Kim Thư - Nguyễn Thùy Gia Ly (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims at conducting a contrastive analysis of conceptual metaphors in the novel Gone with the Wind by Margaret Mitchell and its Vietnamese translational version Cuon Theo Chieu Gio by Vu Kim Thu. The qualitative and quantitative approaches were exploited in order to help the researcher achieve the aims and objective proposed. After examining more than 200 samples in the novel Gone with the Wind of both English and Vietnamese version, we figured out that English and Vietnamese share some expressions of conceptual metaphors of love, life, human, and emotion such as “love is a journey, love is a war, love is a gift/present, love is a fire, love is down, love is a natural force, love is an object, life is a journey, sadness is an illness, emotion is up, sadness is a concrete thing, anger is the heat of a fluid in a container, heart is a container, eyes are container, and human is an animal”. The results of the investigation have pointed out the similarities and differences between two translations. In term of Peter Newmark’s translation, the Vietnamese version “Cuon theo chieu gio” remained fully and more precise to the original story. However, the differences between two cultures lead to some various options of metaphorical expression. The research is also carried out with the hope of adding the voice to the variety of conceptual metaphors, besides giving an in-depth understanding of conceptual metaphors in both versions. In addition, implications of the thesis can be a useful reference for those who are interested in teaching and learning conceptual metaphors.